Introductio ad historiam Europaeam, Latine reddita (ex Officina Guilielmi vande Water, 1693)
De Polonia s. 475-514
a Jo. Frid. Cramero.
Keywords: Papiestwo; historia; Hiszpania; Portugalia; Anglia; Francja; Belgia; Szwajcaria; Niemcy; Dania; Polska; Asyria; Grecja; Macedonia; Rzym